Hubungan Berat Badan Lahir dan Panjang Badan Lahir dengan Kejadian Stunting pada Balita di Salah Satu Puskesmas Wilayah Pesisir Kabupaten Lombok Barat - Siti Rosidah; Muthia Cenderadewi (Malahayati Nursing Journal, 2026)
ABSTRACT Stunting is an irreversible linear growth disorder caused by chronic nutritional deficiency during the first 1,000 days of life. Low birth weight (LBW) and short birth length are important risk factors potentially affecting linear growth in children. To analyze the association of birth length and birth weight with stunting in children under five at a Coastal Community Health Center in West Lombok Regency. An observational analytic study with a cross-sectional design was conducted. A total of 50 children under five were selected from posyandu records in the working area of a coastal community health center in West Lombok Regency using purposive sampling. The independent variables were birth weight and birth length; the dependent variable was stunting status based on the HAZ index (Z-score -2 SD). Bivariate analysis was conducted using Chi-Square test. Of 50 subjects, 26 (52.0%) were stunted. The prevalence of LBW was 32.0% and short birth length was 34.0%. All children with LBW experienced stunting (100%). There was a statistically significant association between birth weight and stunting (χ²=18.983; p0.0001) and between birth length and stunting (χ²=20.952; p0.0001). Low birth weight and short birth length are associated with the occurrence of stunting in children under five in the working area of a coastal community health center in West Lombok Regency. Keywords: Birth Length, Birth Weight, Children Under Five, Nutritional Status, Stunting.  ABSTRAK Stunting merupakan gangguan pertumbuhan linier yang bersifat ireversibel akibat defisiensi gizi kronik pada 1.000 hari pertama kehidupan. Berat badan lahir rendah (BBLR) dan panjang badan lahir (PBL) pendek merupakan faktor risiko penting yang berpotensi memengaruhi pertumbuhan linear anak.  Menganalisis hubungan panjang badan lahir dan berat badan lahir dengan kejadian stunting pada balita di salah satu Puskesmas Wilayah pesisir Kabupaten Lombok Barat. Penelitian analitik observasional dengan desain potong lintang. Sampel berjumlah 50 balita yang diambil dari data posyandu salah satu Puskesmas Wilayah pesisir Kabupaten Lombok Barat menggunakan teknik purposive sampling. Variabel bebas adalah berat badan lahir dan panjang badan lahir, sedangkan variabel terikat adalah status stunting berdasarkan indeks TB/U (Z-score -2SD). Analisis bivariat menggunakan uji Chi-Square.  Dari 50 subjek, 26 (52,0%) mengalami stunting. Prevalensi BBLR sebesar 32,0% dan PBL pendek sebesar 34,0%. Seluruh balita dengan BBLR mengalami stunting (100%). Terdapat hubungan bermakna antara berat badan lahir dengan kejadian stunting (χ²=18,983; p0,0001) dan hubungan bermakna antara panjang badan lahir dengan kejadian stunting (χ²=20,952; p0,0001).  Berat badan lahir rendah dan panjang badan lahir pendek berhubungan dengan kejadian stunting pada balita di salah satu Puskesmas Wilayah pesisir Kabupaten Lombok Barat Kata Kunci: Balita, Berat Badan Lahir, Panjang Badan Lahir, Stunting, Status Gizi.